Translating EU Texts in the English BA Programme: Exploring Teachers’ Views and Practices - Károly, Adrienn (Working Papers in Language Pedagogy, 2014)
Recent research into using translation as a communicative and functional activity in foreign language learning and teaching has pointed out a wide range of benefits for advanced language learners. The research reported in this paper involved teachers teaching translation in the EU-specialisation module integrated into the English bachelor’s degree programme in Hungary. The survey set out to explore teachers’ instructional practices as well as their views and experiences regarding translation. Results indicate that translation in this pedagogical setting is used not merely as a tool to develop language competence and other generic skills, but is regarded as a useful skill in its own right. Translation teachers seem to hold a competence-based view of translation and favour a process-based, functional-textual approach in their teaching practice, which are essential principles in professional translator training. Teachers also emphasise the role of having first-hand translation experience along with a sound theoretical knowledge, which calls for closer collaboration between professional translator trainers and language teachers teaching translation in modern foreign language degree programmes. An important methodological implication of the study is that the investigation of communicative translation teaching outside professional settings can benefit from an interdisciplinary perspective.